Identifikasi Angka Tertularnya Tb Paru Pada Perokok Dan Bukan Perokok Di Puskesmas Rantau Panjang Kabupaten Ogan Ilir Tahun 2022 - Riki Rinaldi (Akper Kesdam I/Bukit Barisan Padang, 2023)
Tuberculosis is a bacterial infection disease caused by Mycobacterium tuberculosis, an acid-fast bacillus that is transmitted through the air. Tuberculosis can spread from one person to another through airborne transmission (sputum droplets from patients with tuberculosis). Pulmonary tuberculosis is a disease with several risk factors, one of which is smoking. Smoking habits play an important role as a risk factor for pulmonary TB disease. The research design used was an analytic survey method with a cross sectional study approach. The time of the research was carried out in August 2022. The place of the research was carried out at the Rantau Panjang Health Center, Ogan Ilir Regency, South Sumatra Province. The sample in this research is 30 respondents. Data analysis using univariate analysis. The results showed that the frequency distribution and percentage of respondents who had smoking habits were 21 respondents (70%) and those who had non-smoking habits were 9 respondents (30%), the frequency distribution and percentage of respondents who were positive for pulmonary TB were 23 respondents (76.6%) ) and negative pulmonary TB as many as 7 respondents (23.4%). Based on the bivariate analysis in this study, it shows that the frequency distribution and percentage of 21 respondents who have smoking habits suffer more from pulmonary TB, namely 19 respondents (90.4%), while of the 9 respondents who have non-smoking habits there are 4 respondents (44 .4%) who were positive for pulmonary TB